The Ability Level of First Grade Secondary Students in Explaining the Scientific Phenomena and Situations Related to Everyday Life - Nawafleh, Waleed; Al-Omari , Wesal; Al-Omari, Ali (Jordan Journal of Educational Sciences, 2018)
The study aimed at revealing first grade students' ability level to explain the scientific phenomena and situations related to daily life. The study further sought to reveal the difference in ability level among students due to their gender and scientific achievement, in addition to the interaction between them, through responding to a test, consisting of (28) items, distributed into two areas: physics and chemistry. The validity and reliability of the test were verified, and then applied to a sample of (323) male and (340) female students from the educational directorate of Kasbat Irbid in the academic year 2016/201. The results of the study revealed that the students' ability level to explain scientific phenomena and situations was low on both areas (physics, chemistry) covered by the test. Also, there were statistically significant differences (α=0.05) in students' ability to explain scientific phenomena and situations attributed to the area covered by the test, in favor of physics. Moreover, there where statistically significant differences in students' ability to explain scientific phenomena and situations on the test as a whole attributed to the academic achievement, in favor of high achieving students. The results also revealed no significant statistical differences in students' ability level attributed to gender and to the interaction between gender and achievement. With regard to each scientific area, the results indicated no statistically significant differences (α=0.05) in students' ability to explain scientific phenomena and situations in chemistry, attributed to students' gender and achievement, but significant differences attributed to the interaction between gender and achievement were not found. In physics, there were statistically significant differences attributed to academic achievement, in favor of high achieving students, compared to those with intermediate and low achievement, whereas no statistically significant differences attributed to gender and to the interaction between gender and achievement were found